Effectively of Fishing Gear Credit Analysis to Fishing Commerce At Wadaslintang Reservoir - Taufik Yulianto; Asriyanto Asriyanto (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2006)
The aim of the research was to describe the management Wadaslintang Reservoir fisheries resources and to analyze the effectivity of the credit by measure of MSY, fMSY, MER and fMER parameters. The result of the measurement in period before giving of fishing gear credit, MSY and fMSY for dominant fishing gear (set gillnet) are 12.253 kg/year and 2.858 effort/year. For dominant fish (Puntius javanicus) which catch by set gillnet, MSY, fMSY, MER, fMER and                  profit are 3.409 kg/year, 3.371 effort/year, Rp 2.046.800,00/year, Rp 620.800,00/year and                                         Rp 1.426.000,00/year.The result of the measurement in period after giving fishing gear credit, MSY and fMSY for dominant fishing gear (set gillnet) are 28.126 kg/year and 11.859 effort/year. For dominant fish which catch by set gillnet, MSY, fMSY, MER, fMER and profit are 4.960 kg/year, 7.043 effort/year, Rp 38.574.500,00/year, Rp 26.678.600,00/year and Rp 11.896.000,00/year. As conclusion, fishing gear credit could be increased the total catch but may decreased the catch per unit effort.   Key words: credit effectively, effort, MSY, MER, gill net